PENGARUH PENGETAHUAN IBU HAMIL TENTANG RISIKO KEHAMILAN DI BAWAH UMUR 20 TAHUN DI WILAYAH KERJA PUSKESMAS GABUS I KABUPATEN PATI - Sri Wahyuni; Wela Anggraini (Universitas Batam, 2022)
The background is the high MMR, and one of the causes of the high MMR is caused by 4 Too (Too young to give birth, Too often give birth, Too close to delivery and Too old to give birth). One of the 4 too is too young to give birth/ young Primi (<20 years old) where at that age there is a risk that threatens the life of mother and baby that most people do not know about. Objective: This study aims to describe the knowledge of pregnant women about the risk of pregnancy under the age of 20 years in the working area of ​​the Gabus 1 Health Center, Pati Regency in 2021. This study used a descriptive method. The population is all pregnant women in the Gabus 1 work area, Pati Regency in 2021, which is 659 people. The sample in this study was obtained by accidental sampling technique amounted to 35 pregnant women. The results of the study were obtained from 35 pregnant women, namely 5 people (14.29%) who experienced pregnancy under the age of 20 years. For the level of knowledge obtained from 35 pregnant women, 5 people (14.29%) with a good level of knowledge, 10 people (28.57%) with a sufficient level of knowledge and 20 people (57.14%) with a low level of knowledge. The conclusion of this study is that most of the knowledge of pregnant women about the risk of pregnancy under the age of 20 years is lacking.